Tomato leaf miner (Tuta absoluta) in the conditions of Azerbaijan - K. G. Huseynov; I. H. Jafarov; H. G. Huseynov; F. B. Musaev (Овощи России, 2023)
Relevance. Among the factors of increasing the productivity and quality of cultivated plants, the correct organization and timely implementation of the fight against harmful organisms is of great importance. At the same time, a special place is occupied by quarantine measures. No less important is the timely detection and destruction of quarantine organisms, their localization and elimination in isolated centers of infection.Methods. The methods for registration testing of pesticides in terms of biological effectiveness (VIZR) and of studying the bioecological features of the tomato leaf miner, adopted by the Scientific Council of the National Institute of Plant Protection and Technical Cultures of the Republic of Azerbaijan, was applied.Results. In the conditions of the South Caucasus in the Republic of Azerbaijan, the biology of the tomato leaf miner, the degree of development, the prevalence and the harmfulness of the insect pest have been studied in detail for the first time. The reasons for the rapid spread of the pest are indicated, the conditions are favorable to it. Listed agrotechnical measures that reduce the population of the pest and measures of biological and chemical control. Employees of the Institute of plant protection and technical crops and the Azerbaijan State Agrarian University have developed a set of measures for monitoring, prevention and pest control, thanks to which it is possible to control the number of pests.